Strategi Public Relation dalam Mengembangkan Citra dan Persepsi Masyarakat Terhadap Pondok Pesantren Islamic Centre Bin Baz (ICBB) Yogyakarta - Syakir, Muhammad Fadlan; Mahmudah, Fitri Nur (Indo-MathEdu Intellectuals Journal, 2023)
Public relations serve as an information and education center that facilitates two-way exchanges between institutions and communities. With established communication, public relations can convey messages about goals, policies, products, or services provided by institutions to the community. In addition, public relations also play an important role in receiving and responding to complaints, aspirations, and public expectations of institutions. This research focuses on public relations strategies in developing public image and perception of ICBB Ponpes using qualitative research types and case study approaches with research methods, interviewing resource persons, namely the Head of Public & Media and Head of the Analysis and Forecasting Prospective Customer Unit. The results showed that Ponpes ICBB has provided examples of effective and efficient strategies in developing a positive image and perception of the community. This can be achieved through systematic planning, management, implementation, supervision of public relations management. By implementing these strategies, Ponpes ICBB has succeeded in establishing good communication with the community, increasing understanding of the objectives and operational activities of pesantren, and responding quickly to community aspirations